SPECIAL SECTION ONE - Beyond Integration: A Re-Evaluation of Migrant and Host Society Relations - Doga Atalay; Umut Korkut; Marcus Nicolson; Peter Scholten; Maggie Laidlaw (Central and Eastern European Migration Review, 2023)
This CEEMR special section examines encounters and interactions between migrants as newcomers and their hosts. Our exploration derives from harnessing, first, a sense of belonging and, second, social interactions as two interrelated processes of encounter. To the extent that the host develops a sense of belonging with the newcomers and cultivates social interaction with them as the others, the newcomers would become visible and encounters followed by meaningful interactions with them would be possible. To look at this from another perspective, the newcomers develop a sense of belonging with their hosts as they encounter them and engage in social interactions with them in their everyday. We note that there is ample research that takes a critical stance on integration and inclusion already but there is still space to explore encounters and interactions in greater detail and why they matter for newcomers and host societies to establish intimacies with each other.